Measuring the costs and benefits of groundwater protection in Cebu City, Philippines - Bagarinao, Ricardo T. (Journal of Environmental Science and Management, 1999)
The threat imposed to groundwater resources by seawater intrusion has become a matter of growing concern among Cebuanos. Groundwater protection strategies were planned and developed to inhibit further inland movement of seawater. The study was conducted to measure the costs and benefits of these alternative groundwater protection strategies. With the objective of reducing the current extraction are to the safe yield of the aquifers, the study considered four alternative strategies, namely: developing surface water, desanilizing saline groundwater, desalinizing seawater, and metering private groundwater extraction. Benefits were measured in terms of avoidance of the decline in the number of service years of productive wells, loss of drinking and cooking water from private wells and, health damage. Estimation employed cost-based approaches and benefit transfer. Results showed that the benefit of protecting groundwater from further intrusion will amount to Php 130.6 million at 1997 prices. among the alternative groundwater protection measures that were considered, reducing the extraction through metering yielded the lowest cost, followed by reducing through the use of surface water. Both strategies yielded positive net present values (NPVs) therefore justifying their implementation on economic grounds. Reducing groundwater extraction through the use of desalted seawater or saline groundwater did not prove to be feasible, yielding negative NPVs